Edaphic oribatid mites in two floodplain forests of central Amazonia: vertical distribution, abundance and soil recolonization after inundation - Franklin, E.; Schubart, R.; Adis, Joachim U. (Revista Brasileira de Biologia, 1997)
Populations of oribatid mites (Acari: Oribatida) were studied in two sites of periodically inundated forests in central Amazonia: one situated in a seasonal igapo-forest, flooded by black- water and a other situated in a seasonal varzea-forest, flooded by white water. Collections were made during the terrestrial phase using the Kempson extraction. Between 0-3,5 cm of soil depth, the ecological indices, density and the species diversity of the edaphic fauna were all low in the varzea in comparison with the 'igapo' forest. The calculated indices also indicated a gradual colonization by adults in the igapo soil. In the 'varzea' the greatest diversity index was recorded in December, indicating that the fauna recovers gradually, but not following a regular pattern as in the 'igapo'. In the 'varzea' Superior Peripheric Oribatida of the Galumnoid group were dominant (50% of the adult population) and in the igapo the Scheloribatidae/Haplozetidae were dominant (45% of the adult population). There were indications that the varzea is more subject to disturbance by both, environmental pressure and human intervention, than the igapo. The indice of similarity between species was very low; also the indice of dominance demonstrated that neither of the common species from both forest was dominant. In comparison with other ecossistems from central Amazonia clear differences between groups of species of Oribatida were detected. The abundance of oribatid mites in tropical forest soils was lower in comparison with soils of temperate forests. Irrespective of the many species found in tropical forests, the majority of them represent the basic Oribatida which are characterize by a low reproductive rate. In contrast, representatives of the periferic higher Oribatida dominate in temperate soils. They have a high reproductive rate which results in a high number of individuals per specie.
Acaros (Acari: Oribatida) Edaficos de duas florestas inundaveis da Amazonia central: distribuicao vertical, abundancia e recolonizacao do solo apos a inundacao
Keywords: Abundance; Floodplain Forests; Inundation; Soil Recolonization; Vertical Distribution; Brazil, Amazonia; Acari; Oribatida